Families’ efforts to secure the future of their children in the context of multiple stresses, including HIV and AIDS - Drimie, Scott; Casale, Marisa (International Food Policy Research Institute, 2008)
Many countries in southern Africa are home to a large number of rural people, dependent on rain-fed agriculture, barely subsisting at poverty levels in years without shocks, and highly vulnerable to the vagaries of the weather, the economy and government policy. Within this context, characterised by a range of multiple stressors on people’s livelihoods, particularly exacerbated by HIV and AIDS, families attempt to plan and act to secure their own livelihoods and the future for their children. Through a review of literature and case studies this paper argues that families are often unable to recover sufficiently from these “entwined” stressors, particularly as HIV and AIDS has undermined their resilience, with the result that they are unable to adequately secure the future of their children beyond immediate needs. Rather short-term demands around basic survival limit choices and with few material resources, inadequate external support and poor access to appropriate services, the long-term welfare of children has become a serious challenge for many families. This argument is explored by looking at issues of family food security, education options and the inheritance of property to underpin the future sustainable livelihoods of children.